ØªØ±Ù‚ÙŠØ© ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ø¨Ø§Ù„Ø±Ø³ÙˆÙ… Ø§Ù„Ù…ØªØØ±ÙƒØ© Ø¹Ù„Ù‰ Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ° Ø¨Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø± Ø§Ù„Ø¹Ù„ÙˆÙ… Ø§Ù„Ø¹ØµØ±ÙŠ Ø¨Ù†Ø¯Ø§ Ø£ØªØ´ÙŠÙ‡ - Mikyal Oktariana (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2014)
MahÄrah kalÄm (speaking skills) is a part of skills that highly considered in learning Arabic at Pesantren Darul Ulum Banda Aceh. It encourages students to practice speaking Arabic on a daily basis both in the classroom and outside. Based on pre observations, there are many students who are unable to speak or communicate in Arabic. Most of them feel tired and bored to learn Arabic due to media being used that does not match with the learning process, while some of them do not practice using Arabic in daily conversation. Based on this situation, the author conducted research using animation media to improve learning speaking skills at the school using action research approach. The results of this study show that the continuity of the learning process with the media is very effective in improving the language proficiency particularly speaking skills. Furthermore, they are also delighted with the use of animation media in the learning process. Keywords: Learning Arabic; Speaking Skills; Animation Media